A qualitative study of patients' experiences of a nurse-led memory clinic. (January 2016) - Stirling, Christine; Campbell, Briony; Bentley, Michael; Bucher, Hazel; Morrissey, Martin
Little is known about patients' decision-making to attend a nurse-led memory clinic (NLMC) or of their experiences in the months following attendance. This paper reports qualitative follow-up data from 13 participants who attended a NLMC run by a Nurse Practitioner, and who were interviewed later in their own homes. Participants attended the NLMC seeking 'benchmarking' against the broader population or confirmation of diagnosis, with the Nurse Practitioner perceived as having more time to talk. Although we anticipated that participants would have changed some behaviours to incorporate 'brain health material', we found that the focus was on maintaining current capacity and lifestyle with most participants delaying planning and decisions about future lifestyle changes until 'necessary'. Understanding why people contact a NLMC and how their participation influences future planning can help us better target health care messages with the aim of improving health literacy.